Strategic database marketing - Hughes, Arthur Middleton (McGraw-Hill, 2012)
Providing the most current marketing theories and strategies for 15 years--now updated to cover digital platforms so you can expand your reach even further! Retaining all the advice, tips, tactics, and strategies that has made it the go-to resource for marketers who take their craft seriously, Strategic Database Marketing now shows how to use marketing metrics, measure them, and predict the most profitable courses of action on Google, e-mail, smart phones, social media, and other websites. Arthur M. Hughes , founder and Vice President of The Database Marketing Institute, Ltd, has been designing and maintaining marketing databases for Fortune 500 companies and others for the past 30 years.
Includes bibliographical references and index. - Print version record
Keywords: Database marketing -- Planning; Bases de données; Marketing; Planification; Database marketing; Planning